Pyoderma gangrenosum affecting the eye, orbit, and adnexa. A review. (2nd January 2018) - McElnea, Elizabeth; Stephenson, Kirk; Fulcher, Tim
ABSTRACT: While pyoderma gangrenosum (PG) most commonly affects the skin it can also involve other organs. It rarely affects the eye, orbit, or adnexa. Its early recognition and proper management with prompt initiation of immunosuppressive therapy are essential for the preservation of the eye and, in turn, vision, in these cases. Here, we review the limited literature already published regarding ocular involvement in PG.